Iraq in the Reports of American Organizations after 2014 and its Impact on Iraqi-American Relations, the Peace Fund Organization is a Model - Najah Mohamed Kazem al-Jazairi , Lect. Dr. Mohamed (Basra studies journal, 2023)
Nowadays, the major countries have moved away from personalization and turned to institutional work to a very large extent, and one of the most important institutions that decision-making institutions rely on are the organizations and strategic thinking centers that rely on a lot. The United States of America is considered the leader today in the field of establishing and employing strategic thinking centers in formulating its comprehensive strategy as well as in determining the mandates of that strategy. Perhaps the emergence of the fund for PEACE organization came in line with the requirements and needs of the United States government in terms of identifying and diagnosing the countries of the world with respect to the level and quotient of fragility of those countries according to a division of: 11) standard, according to which an increase in the number of The partnerships concluded by the American institutions and ministries and the mission with this organization, the interaction and activation of the role of the United States and foreign relations were also diagnosed according to the information and conclusions provided by this aforementioned organization through the annual reports and other publications of the organization. According to the foregoing, Iraq is not a special case or far from application or adoption of the recommendations of the organization by the United States of America. On the contrary, the latter considers Iraq an important and main part when announcing the American strategy towards the Middle East region, and as previously mentioned, this strategy is defined Through it, bilateral relations are woven according to consultations and reports from organizations and strategic think tanks, including the Fund for Peace Organization (F. F. P.), which gave Iraq importance that corresponds to its geopolitical role and geo-strategic status, and therefore these reports and consultations will certainly be reflected in relations US- Iraq. The research delves into these relationships, and the impact and influence of the Fund for Peace organization on those relationships, positively or negatively.